Studies On The Utilization And Supplementation Of Sweet Corn Stover Silage And Its Effect On Carcass Composition Of Growing Lambs - Mohd Ali, Yacob (1994)

(untitled)
The main objectives of this study are to determine the growth performance and carcass composition of growing lambs raised on sweet corn stover silage. The sweet com stover can be considered to be a better quality animal feed as indicated by its high crude protein content and its low neutral detergent fibre, acid detergent fibre and acid detergent lignin as compared to other cereal crop straws. The nutrient content of the sweet com stover could be maintained by ensiling. The ensiling process takes four weeks and the silage can be stored for 16weeks without any change to its nutritive value. When rice bran is added to the ensiling, the crude protein and the potential degradability increase. However, addition of molasses only increased potential degradability but decreased crude protein content. The total intake of sweet com stover silage by growing lambs was 24.2 g dry matter/kg body weight. The concentration of rumen ammonia was 229.2 mg Nil and the total volatile fatty acids was 63.1 mM/i. With concentrate supplementation (200 g/animal/day; 20 - 30% crude protein, fish or soybean meals as source of protein) on the sweet corn stover silage basal diet, the total dry matter intake increased (29.0%), however, dry matter intake of sweet corn stover silage decreased ( 1 3 .6%). The concentrate supplementation also increased rumen ammonia (28. 1 %) and total volatile fatty acids (5.5%). Providing 100% of the sweet corn stover silage to the lambs was sufficient for maintenance as well as for a little average daily gain (10.7 g/day) with a dressing percentage of 42.5%, carcass fat of 3.3% and lean to bone ratio of 1.86:1.The concentrate supplementation increased the average daily gain to 7l.6 g/day, the dressing percentage to 47.7%, the carcass fat to 8.3% and the lean to bone ratio to 2.8: l . Fish meal or soya bean meal as a source of protein supplementation had a similar effect on the nutritive values, growth rate and carcass composition.